Monitoring and learning for country-level portfolio decision-making and adaptation - and Buffardi, Anne L; Mason, Paige; Hutchings, Claire; Sharp, Samuel (ODI/GLAM, 2019)
Most measurement and adaptive management approaches were developed for and from individual projects. This briefing aims to guide measurement and management of country-level portfolios of work. It identifies potential purposes portfolio-level analyses can fulfil, types of adaptation, and the relative role of monitoring, learning and evaluation (MEL). Drawing on reviews of practice from the United States Agency for International Development (USAID) and the United Kingdom Department for International Development (DFID), guidance notes, and experiences of members of the Global Learning for Adaptive Management (GLAM) initiative, it offers recommendations and considerations that are particularly relevant for this level of analysis and management. Key messages - Portfolio-level analyses can serve eight potential purposes, each of which answers different questions, involves adaptation at different times and levels, and requires different types of evidence. Identifying the purpose(s) and how the component parts relate to each other should guide the development of monitoring and learning systems. - Portfolios are oriented more towards breadth than depth, involve more people with different perspectives, and draw on multiple sources of evidence with potentially greater variation in quality. - In practice, four activities appear to be applied most frequently at a portfolio level: alignment of indicators and aggregation of monitoring data; synthesis of multiple sources and types of information to provide a summary of outputs, outcomes, common observations and trends; periodic review and reflection sessions; and strategic planning, design or refresh of the portfolio strategy. - The extent to which evidence-informed portfolio management is facilitating learning and adaptation has not been well documented to date, and we suggest potential indicators to do so.